2009
DOI: 10.1016/j.bbmt.2009.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Intensified Conditioning and Tapering of Prophylactic Immunosuppressants for Graft-versus-Host Disease in Allogeneic Hematopoietic Stem Cell Transplantation for Refractory Leukemia

Abstract: For patients with advanced leukemia undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT), a major obstacle to success, especially in those with a high leukemia cell burden, is relapse of the underlying disease. To improve the outcome of allo-HSCT for refractory leukemia, we investigated the strategy of sequential intensified conditioning and early rapid tapering of prophylactic immunosuppressants therapy for graft-versus-host disease (GVHD) during the early stage after transplantation. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…To maintain consistency of primary disease category and minimum follow-up (12 months) between the study and historical groups, we removed 6 patients with chronic myelogenous leukemia with blast crisis (CML-BC) from historical data, and re-analyzed historical data on December 31, 2009 [15]. A total of 48 refractory acute leukemia undergoing allo-HSCT but not receiving DLI from May 2001 to December 2008 were enrolled in the historical group (patient's characteristics as shown in Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To maintain consistency of primary disease category and minimum follow-up (12 months) between the study and historical groups, we removed 6 patients with chronic myelogenous leukemia with blast crisis (CML-BC) from historical data, and re-analyzed historical data on December 31, 2009 [15]. A total of 48 refractory acute leukemia undergoing allo-HSCT but not receiving DLI from May 2001 to December 2008 were enrolled in the historical group (patient's characteristics as shown in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We previously introduced a strategy of sequential intensified conditioning, consisting of fludarabine (Flu)/cytarabine (Ara-C) salvage chemotherapy followed by TBI/CY/etoposide (VP-16) myeloablative conditioning, and early rapid tapering of immunosuppressant for inducing GVL in refractory advanced leukemia undergoing allo-HSCT [15]. The results indicated that this strategy had an acceptable toxicity profile and improved outcome for refractory leukemia, with 5-year overall survival (OS) and disease-free survival (DFS) of 44.6% and 38.2% [15]. Despite these encouraging results, relapse in our cohort was still considerable, with 3-year relapse rate of 33.3% [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditioning regimens included: (1) total body irradiation (4.5 Gy/day, on days -5 and -4) + cyclophosphamide (60 mg/kg/day, on days -3 and -2) in 38 recipients; (2) busulfan (3.2 mg/kg/day, on days -7 to -4) + cyclophosphamide (60 mg/kg/day, on days -3 and -2) in 39 recipients; (3) busulfan (3.2 mg/kg/day, on days -6 to -3) + fludarabine (30 mg/m 2 , on days -6 to -2) in 21 recipients, and (4) fludarabine (30 mg/m 2 , on days -10 to -6) + moderate-dose cytarabine (2 mg/m 2 , on days -10 to -6) + total body irradiation (4.5 Gy/day, on days -5 and -4) + cyclophosphamide (60 mg/kg/day, on days -3 and -2) + etoposide (600 mg/day, on days -3 and -2) in 8 recipients [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Few studies have investigated survival in refractory acute leukemia after sequential treatment with chemotherapy and a myeloablative or non-myeloablative conditioning regimen for allo-HSCT [8][9][10]; however, high frequencies of relapse and treatment-related toxicities present major obstacles to survival. To overcome these drawbacks, we decided to administer DNR/VCR/PSL in anticipation of debulking of leukemia, followed by allo-HSCT using a conditioning regimen with VP/CY/TBI.…”
Section: Discussionmentioning
confidence: 99%